Initiation of interdisciplinary prevention rounds: decreasing CLABSIs in critically ill children - Matthew Linam; Lisette Wannemacher; Angela Hawthorne; Christina Calamaro; Patrick Spafford; Karen Walson (Cambridge University Press, 2024)
Abstract Objective: Central line-associated bloodstream infections (CLABSIs) harm children. Insertion and maintenance bundles have significantly reduced CLABSIs, but infections still occur. The objective was to develop bedside infection prevention (IP) rounds and evaluate their impact on CLABSI rates. Methods: This quality improvement project was initiated sequentially in the neonatal intensive care unit (NICU) and pediatric intensive care unit (PICU) of a large academic children's hospital. IP rounds, interdisciplinary discussions led by the hospital epidemiologist and unit nursing leader with the bedside nurse, occurred weekly for patients with central lines. Discussions included strategies to optimize line maintenance and identify and mitigate patient-specific infection risks. Concerns and recommendations were communicated with the clinician. CLABSIs were identified by prospective surveillance using standard definitions. The change in CLABSIs over time was analyzed using days-between-events charts (g chart). Results: IP rounds included 3,832 patients in the NICU and 1,322 patients in the PICU. Opportunities were identified to reduce line access and protect the dressing from contamination. The average days between CLABSIs in the NICU increased from 41 days to 54 days after IP rounds began. The longest time between CLABSIs was 362 days. In the PICU, the average days between CLABSIs increased from 53 to 91 days. The longest time between CLABSIs was 398 days. Conclusion: IP rounds reduced CLABSIs in the NICU and PICU by reinforcing best practices, encouraging proactive strategies, and fostering communication between members of the healthcare team.